A DRUG REVIEW ON EFFICACY OF ‘PEREECHANGAI NEI’ A CLASSICAL SIDDHA DRUG IN THE MANAGEMENT OF MADHUMEGAM (TYPE 2 DIABETES MELLITUS) (International Journal of Ayurveda and Pharma Research, 2019)
In Siddha system of medicine, diseases are classified into 4448 types. According to Yugi Vaithiya Chinthaamani, a siddha classical text Meganoi is classified into 20 types based on three humors Vatha, Pitha, Kabha. Madhumegam is one among them, which comes under Pitha type called Thithippu Neer. The causes, signs and symptoms of Madhumegam could be correlated with Diabetes Mellitus in modern system. Mathumegam is a clinical condition characterized by frequent and excessive passage of urine with ‘sweetness’ eventually leading to deterioration of seven body constituents. Its deterioration causes Avathaigal which are described as complications of long term poorly controlled hyperglycemia. Diabetes mellitus is one of the major health problems in most developing countries. Being a lifestyle disorder its management is still a challenge for modern system of medicine. Increase in the number of diabetic patients, high cost for medical treatments, unsatisfactory treatment response are the major reasons for people to switch over to traditional medicinal systems. At current scenario, Siddha system among Indian systems of medicine is gaining more attention globally and it serves as a hope in controlling this dreadful disease and preventing its high risk complications. Siddha drugs include herbal, mineral and herbo-mineral drugs. Among which pure herbal medicines serve the purpose in the management of chronic diseases like Madhumegam for long term use. This review article focuses on one such polyherbal Siddha formulation ‘Pereechangai nei’ as mentioned in text Therayar Maha Karisal, specifically indicated for Madhumegam.